The use of the endoprosthesis of the first plusnephalanx joint of the original design (clinical case) - G. P. Kotelnikov; A. A. Nurakhmetov; K. B. Tazhin; A. N. Nikolaenko; A. P. Borisov (Acta Biomedica Scientifica, 2025)
Background. Currently, the replacement surgery of the first metatarsophalangeal joint (MTP joint) is considered to be one of the effective, invasive method for treating severe forms of osteoarthritis of the MTP joint. However, there are a number of postoperative complications that may be caused by the prosthesis itself. Research in this area can provide valuable information that will assist specialists in making decisions regarding the most suitable implant for each patient. Additionally, improvements in the design of implants for MTP joint replacement and further studies will help make them more effective, durable, and biocompatible. The aim. To present a clinical case of osteoarthritis of the first metatarsophalangeal joint (Hallux rigidus) treated surgically by conducting total joint replacement with a monolithic ceramic implant featuring an optimal stem design. Materials and methods. A clinical case is a 47-year-old patient presenting with deforming osteoarthritis of the 1st MTP joint. It was managed by arthroplasty of 1st MTP joint using an all-ceramic endoprosthesis with an optimal leg (RU № 226697). Results. Three months after the operation, the pronounced significant increase in the range of movement and pain reduction in the 1st MTP joint were observed. Positive dynamics was preserved 6 and 12 months postoperatively. Conclusion. The results of the surgery indicate that the replacement of the first metatarsophalangeal joint replacement using a monolithic ceramic implant with an optimal stem design is efficient surgical intervention. This approach significantly not only alleviates pain, but improves the quality of life for patients overall. However, to fully assess the long-term results and sustainability of the achieved effects, further studies are needed to analyze the distant outcomes of this intervention.